La escritura como proceso: metodología para la enseñanza de la expresión escrita en español como segunda lengua. - Madrigal Abarca, Marta (2012)
In this course I will present the results of an investigation into a pedagogical strategy for the teaching of written Spanish to non native students. The outcome of which is focused on the process rather than the product. This methodology is centered on distinct upper level thinking activities used by the writer to compose a text. It takes into account the complete period time, which begins when a circumstance is created which stimulates the idea for the production of the text and all the way through until it is finished. Within the scope of this process the final version of the text or product is demonstrated, but more important is the description and the learning of all the intermediate steps and strategies which can be utilized in the writing. In this way the process includes three stages: the pre-writing phase, first drafts and revisions. There is equal and vital importance given to the roles played by both students and teachers in this process.